Analysing key relationships: digitalization, innovation and structural conditions in EU - Félix Hernández de Rojas; Pilar Rodríguez Pita; Jorge Emiliano Pérez Martínez (International Telecommunications Society (ITS), 2023)
There is an intrinsic relationship between innovation and digitalization, marked by the specific and structural socioeconomic characteristics of our regions and countries. These characteristics explain the territory heterogeneity and determine in many cases specific paths for the next digital transformations in the EU. The EU is answering this movement with an ambitious multimillion public investment, the NextGeneration Funds, and an ample set of policies to encourage its digital 2030 agenda: innovation is in front line, governing most of the decision for countries' digitalization under our specific set of European values (Hajighasemi et al., 2022) But there are some tough questions countries cannot ignore: are all these economical efforts around innovation well addressed to foster digital transformation? To what extent a country offers a different behavior across this intime relationship between digitalization and innovation? In which aspects higher degrees in innovation means a higher advantage for the economic and social digitalization in a country? Innovation, as it is broadly defined in the European Innovation Scoreboard (EIS), published by European Commission, is a complex concept built by a multitude of interacting aspects that do not necessarily work synergistically: a framework of conditions, innovation activities, investment, and economics impacts. The consequential results of cross-cutting drivers, such as digitalization, is often difficult to assess, as the achievement of certain targets may also inadvertently hinder progress towards others. Although digitalization in economy implies positive relationship with technological innovation (Yuan et al., 2021), and digital transformation boosts companies' innovation and performance (Ferreira et al., 2019), other results show that besides improving the level of business digitalization, innovation has a direct influence on business performance, as well as acting as a moderating variable that should be aligned with strategy (Fernández-Portillo et al., 2022). However, other research shows that innovation activities do not necessarily imply technological improvements (Zabala-Iturriagagoitia et al., 2021). Our study describes a comprehensive and systematic European country-based analysis of statistical associations between both, digitalization and innovation indicators operating at several different levels to understand better these apparent contradictions. We use for this study a regression and some graphical analyses, using open data coming from EIS and DESI (Digital Economy and Society Index), this last one used by the European Commission to measure countries' digitalization in Europe. Also, we have considered structural economic indicators which complement the EIS related to country's wealth, population and rule of law, business activity, innovation enterprise segmentation and environmental factors. (...)
Keywords: 330